Manajemen Pembelajaran Berbasis Projek Penguatan Profil Pancasila Dimensi Mandiri dan Bergotong Royong di Sekolah Dasar - Asiyah, Siti; Sudana, I Made; Soedjono, Soedjono (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This research was carried out at SD Negeri Petung, Pageruyung District, Kendal Regency, which aims to describe the process of planning, organizing, implementing and evaluating project-based learning to strengthen the Pancasila learning profile (P5) in the independent and mutual cooperation dimensions. This research is qualitative research with a descriptive analytical approach. The data collection techniques used were interviews, observation and documentation studies. Informants in this research include: Principal, teachers, and students, guardians of students. The results of the research (1) planning are 1) Developing the School's Vision, Mission and Goals; 2) Prepare RKJM, RKT, RKAS; 3) Designing dimensions, themes and time allocation; 4) Create a project priority activity module; 5) planning assistance in project implementation; 6) carry out evaluation and follow-up. (2) Organizing is 1) formation of management, 2) division of work tasks according to potential, 3) Standard SOPs for implementing tasks 4) Coordination and Communication in all fields. (3) Implementation includes 1) introduction 1 which contains the meaning and history of plastic, how to use plastic, how to use plastic wisely; 2) introduction stage 2 which includes the use and management of plastic, management and processing of plastic waste, an attitude of responsibility for sustainability; 3) assessment; 4) evaluation, reflection and follow-up. (4) Supervision of Petung includes internal supervision carried out by the school principal and supervisor, external supervision by the school committee. Apart from that, supervision of 1) assessment standards; 2) assessment; 3) the results of the assessment are in the form of a project report; 4) follow-up of project activities. Keywords: Project Management Strengthening the Profile of Pancasila Students, Independent and Collaborative Dimensions Collaboration